The Relationships between Information and Practices of Teaching Staff that Give Courses at Educational Programs during the COVID 19 Pandemic with Regards to Distance Learning - Terkan, Remziye; Ucar, Onder (International Review of Management and Marketing, 2020)
In this study the correlation between information and practices of teaching staff that give courses at educational programs during the Covid 19 pandemic with regards to distance learning was analyzed. 88 teaching staff working at two different universities, Fifteen November University of Cyprus and Near East University, and who gave distance learning lessons during the Covid 19 pandemic participated in this study. The Nicosia district of the Turkish Republic of Northern Cyprus was chosen as hub where 88 Teaching Staff were contacted at 2 universities based on an appropriate sampling method. While some of these 88 Teaching Staff fully answered the questions of the study, some of the Teaching Staff provided limited answers to the questions of the study. The study was designed as a blended research model so as to incorporate both qualitative and quantitative research methods at the same time. In order to correctly analyze data descriptive statistics including frequency, percentages, arithmetic means and standard deviation, as well as the Anova test were used. Keywords: Distance learning, the Covid 19 pandemic, distance learning practices, North Cyprus JEL Classification: D83 DOI: https://doi.org/10.32479/irmm.10765